The effect of regrinding on the design of flotation circuits. (1st September 2020) - Acosta-Flores, Renato; Lucay, Freddy A.; Gálvez, Edelmira D.; Cisternas, Luis A.
Graphical abstract: Highlights: The uncertainty in regrinding stages on the design of flotation circuits is analyzed. The hypothesis "there are few optimal circuit structures when regrinding is included" was tested. Proof by construction and proof by exhaustion are used to test the hypothesis. Results obtained allow us to confirm the hypothesis. Abstract: The regrinding of some streams within flotation circuits, to liberate valuable mineral attached to gangue, is a common practice. However, the methodologies proposed for flotation circuit design based on optimization, usually, do not consider regrinding. This work analyzes the effect of the uncertainty in flotation and regrinding stages on the design of flotation circuits via mathematical optimization. We postulate that there are few optimal circuit structures when regrinding is included in the design problem under uncertainty. Two methods of proof are used to confirm the postulated hypothesis: proof by construction and proof by exhaustion. Results obtained allow us to confirm the hypothesis, which allows separating the design of the flotation circuits into two steps. First, a set of optimal structures are determined. Second, the equipment design parameters and operating conditions are determined through simulation and laboratory tests.